O discurso sobre violência e indisciplina no currículo do PROERD: tramas para pensar a governamentalidade - Oliveira, Gislaine Félix de (2020)
This research has as its central focus the analysis of the discourse on violence and indiscipline in the 5th year curriculum of the elementary of the Educational Program for Resistance to Drugs and Violence – PROERD, offered to children and adolescents from public and private schools in Brazil. The analysis seeks to understand the discursive mesh present in this curricular document and how this process ends up producing conditions for the government of itself and of others in a process of governmentality. The research stands out as qualitative, bibliographic survey and data and document analysis were carried out, as well as an interview given by police officers who organized the project here in Rio Grande do Norte. We adopted Michel Foucault (2011, 2012, 2014a) to operate on the concepts of discourse, power and knowledge relations, normal, abnormal, discipline and indiscipline and also governmentality. PROERD, through its applications in the curriculum field, acts with a discourse of prevention and combating the use and trade of drugs and violence, but it is up to reverberating behaviors that show behaviors considered abnormal, control and, thus, determining ways of being and Act. Using the safety device, students are led to a government that is justified for good: Governmentality.